(untitled) (Intent Research Scientific Journal, 2023)
This scientific article is devoted to the study of the process of creating a national character on the theater stage. Theatrical art, as one of the main forms of cultural expression, plays an important role in the formation and transmission of cultural characteristics and identities of different peoples. The article analyzes various aspects of creating a national character, including dramaturgy, acting, directing and artistic solutions.